Association between dietary index of gut microbiota and constipation in a female population: a cross-sectional study - Lu, Wangfeng; Feng, Gang; Liu, Lei; Ding, Qi (Frontiers in Nutrition, 2025)
ObjectiveTo examine the potential association between dietary index of gut microbiota (DI-GM) scores and constipation in adult women in the United States.MethodsThis cross-sectional study used data from adult participants in the 2005–2010 US National Health Survey (NHANES). The missing values in the covariables were filled by multiple interpolation. Multivariate logistic regression models were used to determine the odds ratios (OR) and 95% confidence intervals (CI) for the association between DI-GM and constipation. Subgroup analyses were also performed to examine the possible interactions between DI-GM and constipation.ResultsOf the 7,325 subjects, 887 reported constipations, with a prevalence of 12.1%. After adjustment for multivariate modeling, the DI-GM score was significantly associated with constipation (0.92 [95% CI 0.87–0.96]; p = 0.001). Similar results were found for the association of beneficial gut microbiota score with constipation (OR 0.89 [95% CI 0.84 to 0.95]; p = 0. 001). Subgroup analyses revealed that the relationship between DI-GM scores and constipation remained stable (p > 0.05).ConclusionDI-GM was negatively associated with the incidence of constipation in the female population. Clinicians should consider the influence of dietary structure on the treatment of constipation in women. Dietary intervention can be an important strategy for the comprehensive treatment of constipation.